Teacher Candidates’ Use of Inclusive Children’s Literature in Interactive Read-Alouds: Successes, Challenges and Implications - Francesca Pomerantz (Education Sciences)
Book banning and laws against discussing so-called “divisive concepts” in the United States are limiting what is read to children in schools, even in places without specific legislation. Books by Black and LGBTQIA+ authors and/or about Black or LGBTQIA+ characters are specific targets of the book banning and censorship efforts. The research reported in this article used a case study approach to explore two teacher candidates’ responses to inclusive children’s picture books and their discussions of the books with students in their classrooms during their practicum. The results indicated that the teacher candidates strongly believed in the value of sharing inclusive children’s literature and effectively utilized open-ended questions to spark critical thinking. However, they found it challenging to follow their students’ leads and build on comments in ways that could have resulted in deeper thinking and understanding. More practice, feedback and reflective opportunities are needed during teacher preparation in actual classrooms to improve teacher candidates’ abilities to conduct interactive read-alouds about topics that feel risky. The findings also highlight the need for schools and mentor teachers to model discussions about inclusive children’s books.